Assessing the Accuracy in Transcribing the International Phonetic Alphabet (IPA) of BSED-English Majors - Talaroc, Jenny Mae; Bantac, Michelle; Canacan, Nadine; Gaan, Dayanara; Naparan, Genesis (Universitas Kapuas, 2025)
Pronunciation is crucial as it plays a huge role in expressing ideas and avoiding communication misunderstandings. However, some students face challenges with pronunciation, especially in ESL (English as a second language), and several studies have noted that phonetics can help address pronunciation errors through the International Phonetic Alphabet (IPA). Considering that no prior research has explored the accuracy level of BSED-English majors in transcribing IPA, therefore, this study evaluates the accuracy of BSED-English majors in assessing their accuracy level in transcribing the International Phonetic Alphabet, given their exposure to the IPA symbols in one of their courses. The study used a quantitative descriptive research design, and it was conducted in a private educational institution in Pagadian City, Zamboanga Del Sur, with 39 participants from the BSED-English program. The validated instrument consisted of 41 words (consonants, vowels, and diphthongs) that they needed to transcribe into IPA symbols. The results revealed that transcription accuracy across all categories “did not meet expectations,” with consonants (15.17%) higher than vowels (11.57%) and diphthongs (13.67%). Common transcription errors were identified, and the result shows a significant difference in the accuracy levels across the three categories using the one-way ANOVA, therefore rejecting the hypothesis. Thus, the findings can be effectively examined through the Perceptual Assimilation Model, in which learners assimilate unfamiliar sounds to sounds they already know in their native language, and the lack of familiarity and practice in IPA transcription, which explains why BSED-English majors face common errors when transcribing a word.